(untitled) (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2024)
My paper focuses on the problem of empathetic response in immersive experiences concerning global warm- ing issues. Following a rich scientific production, which points out the idea of virtual reality as both “the ultimate empathy machine” – as firstly stated by filmmaker Chris Milk – and a promising tool to promote ecological awareness, my essay presents, in the first place, the main characteristics of immer- sive experiences concerning the issue, showing how viewers interact with the environment from the perspective of presence, and body ownership. As describing potentials and limits of empathetic response in virtual environments, I draw attention to the fact that now it is impossible to build virtual reality expe- riences that fully embody the essence of global warming, as it is intrinsically an hyperobject – a term I take from Timothy Morton’s philosophical approach towards environmental issues. In this framework, the purpose of my essay is to uncover the impossibility to represent global warming faithfully if we keep on conceive immersive experiences in the way we are doing now. What I propose is a radical change in our idea of virtual reality when it comes to represent global warming.